2015
DOI: 10.9775/kvfd.2015.12978
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Black Cumin Seeds (Nigella sativa L.) or Black Cumin Oil Addition to Japanese Quail Diets on Growth Performance, Carcass Traits and Some Blood Parameters

Abstract: Bu çalışma, bıldırcın rasyonlarına çörek otu tohumu ya da çörek otu yağı ilavesinin besi performansı, karkas özellikleri ve bazı kan parametrelerine etkisini belirlemek amacıyla yapıldı. Araştırmada, 180 adet bir günlük yaşta Japon bıldırcını civcivi kullanıldı. Civcivler 45 hayvandan oluşan 4 ana gruba, her ana grup ise 15 civcivden oluşan 3 alt gruba ayrıldı. Gruplardan birisi başlangıç (1-21. gün) ve büyütme (22-35. gün) dönemlerinde temel yemlerle beslendi (Kontrol). Diğer gruplar aynı yeme %0.1 oksitetras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Our findings concur with those of Nuengjamnong and Angkanaporn (2018) , who observed that including COS in broiler diets significantly enhanced the ratio of villus height to crypt depth while decreasing crypt depth. Moreover, Tufan et al (2015) reported that Japanese quail-fed COS had considerably longer villus and crypt lengths than the control group. Moreover, Kamal et al (2023b) obtained that growing rabbits fed COS had more villi and deeper crypts than control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings concur with those of Nuengjamnong and Angkanaporn (2018) , who observed that including COS in broiler diets significantly enhanced the ratio of villus height to crypt depth while decreasing crypt depth. Moreover, Tufan et al (2015) reported that Japanese quail-fed COS had considerably longer villus and crypt lengths than the control group. Moreover, Kamal et al (2023b) obtained that growing rabbits fed COS had more villi and deeper crypts than control animals.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in both male and female quails, the thigh percentage increased in the NS-0.5 group compared to the control and other NS-supplemented groups; Also, the abdominal fat ratio decreased with the supplementation of NS.Therefore, considering that the quails closest to the group mean were slaughtered, it can be stated that in terms of carcass characteristics,compared to other NS-added groups, the best results were achieved in the NS-0.5 group and the rate of NS supplement was significant in this respect. Consistent with the results of this study, Majeed et al (2010) determined that the supplementation of 0.5% NS to broilers diet increased the thigh percentage but did not affect the breast weight.In different studies conducted with quails; Karadagogluet al ( 2019) found that supplementing the diet with 1% and 2% NS did not affect the slaughter weight, hot carcass weight, heart, and liver weight; Arif et al (2018) found that the supplementation of 0.5% black cumin powder to the diet did not affect liver, gizzard, heart and thigh weights; Tufan et al (2015) found that the supplementation of 1% NS did not affect carcass yield, breast, thigh and wing ratios. These results are consistent with the result of the present study that supplementation of 0.5%, 1%, and 2% NS to the diet did not affect slaughter, hot carcass, wing, liver and heart weights, compared to the control group.In some studieswith broilers; Amadand Mohammed(2013) found that the addition of 1.5%, 2.5%, and 3.5% NS did not affect slaughter weight, carcass yield, and edible visceral rates; Kumar et al (2018) stated that slaughter weight, carcass yield, breast, thigh, wing, neck, liver, and abdominal fat weight, and total edible visceral weight increased or tended to increase with the addition of 0.5%, 1% and 2% black cumin Although kidney MDA values showed a tendency to decrease in the NS groups, this decrease was not significant compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…While Hamedi et al (2014) stated that villus height increased and crypt depth decreased in broiler chickens with NS supplementation, Saeid et al (2013), on the other hand, stated that both the villus height and the crypt depth increased in quails with 0.5% black seed supplementation. In the literature, there are mostly studies examining the effects of using NS in quail feeds on the performance, food digestibility and economic efficiency of quails (Karadagoglu et al, 2019;Tufan et al, 2015). In addition, in previous studies, serum oxidant and antioxidant levels of NS in broiler feeds were examined (Aydogan et al, 2020;Hassan, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Saleh (2014) reported significant improvement in LW and LWG of chicks when they were fed 1 ml/kg DM of BCS oil compared with chicks in an unsupplemented control group. Similarly, when broilers were fed a diet that was supplemented with 0.10-0.15% BCS oil (Attia & Al-Harthi, 2015) and when Japanese quail were a diet that was supplemented with 0.1% BCS oil (Tufan et al, 2015) the LWG of the birds was significantly increased. In the current study, both diets supplemented with BCS oil generally increased LW and LWG.…”
Section: Tablementioning
confidence: 99%